Correlation and path analysis in blackgram (Phaseolus mungo) - SINGH, GYANENDRA; SINGH, MAJOR (The Indian Journal of Agricultural Sciences, 2013)
Fifly-two genetically diverse genotypes of black gram (Phaseolus mungo L.) were grown during rainy seasons (kharif) of 1990 and 1991 to study the correlation and path analysis among 9 morpho-agronomic characters. Significant differences were observed fur all the 9 characters. Grain yield had significant and positive association with 100-seed weight, pods/plant, pod length and plant height. Path analysis indicated that 100-seed weight and pods/plant had high direct effect on grain yield, showing that these characters were the main yield determinant and could be taken as an index to improve the seed yield through seleclion.